The MOZ Histone Acetyltransferase in Epigenetic Signaling and Disease. Issue 11 (November 2014) - Carlson, Samuel; Glass, Karen C.
<x xml:space="preserve">Abstract</x> The monocytic leukemic zinc finger (MOZ) histone acetyltransferase (HAT) plays a role in acute myeloid leukemia (AML). It functions as a quaternary complex with the bromodomain PHD finger protein 1 (BRPF1), the human Esa1‐associated factor 6 homolog (hEAF6), and the inhibitor of growth 5 (ING5). Each of these subunits contain chromatin reader domains that recognize specific post‐translational modifications (PTMs) on histone tails, and this recognition directs the MOZ HAT complex to specific chromatin substrates. The structure and function of these epigenetic reader modules has now been elucidated, and a model describing how the cooperative action of these domains regulates HAT activity in response to the epigenetic landscape is proposed. The emerging role of epigenetic reader domains in disease, and their therapeutic potential for many types of cancer is also highlighted. J. Cell. Physiol. 229: 1571–1574, 2014. © 2014 Wiley Periodicals, Inc.